Reductive microenvironment responsive gadolinium-based polymers as potential safe MRI contrast agents. (18th February 2019) - Guo, Shiwei; Xiao, Xueyang; Wang, Xiaoming; Luo, Qiang; Zhu, Hongyan; Zhang, Hu; Li, Haonan; Gong, Qiyong; Luo, Kui
Abstract : A ROX and enzyme-responsive biodegradable gadolinium-based mCA was prepared, demonstrating a short gadolinium retention time and sufficient MRI contrast efficacy in tumors. Abstract : Accumulation of nano-scale contrast agents in body tissues potentially induces adverse effects associated with free Gd(iii ) ion release from the nano-scale system, such as nephrogenic systemic fibrosis and gadolinium deposition in the brain tissue. A novel formulation strategy was proposed herein for Gd-based macromolecular MRI contrast agents (Gd-mCAs), which may significantly reduce Gd(iii ) retention but maintain sufficient imaging contrast. Biodegradable poly[ N -(1, 3-dihydroxypropyl)methacrylamide] copolymers (pDHPMA) were synthesized from N -(1, 3-dihydroxypropyl)methacrylamide (DHPMA) as a monomer and enzyme-responsive short peptide (GFLG) as a chain transfer agent. Small molecular Gd-chelate (Gd-DOTA) was conjugated onto the copolymer backbone through a sulfide bond or a GSH-sensitive cleavable disulfide bond to produce two novel Gd-mCAs (pDHPMA-Cy5.5-DOTA-Gd or pDHPMA-Cy5.5-SS-DOTA-Gd) for tumor diagnosis. Their relaxivities were 10.49 and 10.24 mM −1 s −1 respectively, which were significantly higher than that of DTPA-Gd (3.97 mM −1 s −1 ). Compared with pDHPMA-Cy5.5-DOTA-Gd, pDHPMA-Cy5.5-SS-DOTA-Gd had a shorter Gd(iii ) retention time but maintained a sufficient contrast efficacy. We have demonstrated that the conjugation of small molecular Gd-chelate to biodegradable macromolecular carriers through a ROX-sensitive biocleavable disulfide bond may be an efficient strategy for formulating safe biodegradable Gd-based pDHPMA copolymers as MRI contrast agents.